Poverty and land access in Igbo land Nigeria: implications for policy and Agroenterpreneurship development (2013)
Household livelihood across Africa 50 years after independence have recorded lean improvements especially in terms of access to essential production inputs. Household rate of land access, means of access, Household rate of land access, means of access, welfare and investment capacities, land cost and the linkage between access to land and the above measured parameters were investigated using a set of questionnaires administered to urban and rural settlements. Descriptive results showed that poverty incidence was high (60%) especially in rural areas is distant from expectations of the MDGs. Lands were obtained majorly through land purchase indicative of growing land commercialization whose cost (per ha.) ranged from N500,000 to N1m. Access to land (in rural, urban settlements) had low positive correlations with age in both settlements (0.181, 0.163), with education (0.183, 0.25) and welfare capacity (0.25, 0.82). Similarly, regression line showed negative slopes, low but positive coefficients (R2) with welfare poverty (R2=0.041) and investment poverty (R2=0.017) indicating limiting influence of different poverty forms to livelihood and household productivity. Periodic review of land administration, unified land policy thrust along the lines of reviving interest especially among youths in agriculture through incentives (tuition-free agricultural disciplines), implementation synergy, capacity building and granting of loans as financial safety net are key achievable policy options.